Development of a dental caries monitoring card to prevent stunting in children elementary school - Riyadi, Slamet; Nurmawi, Yesi; Febrianti, Sri; Salfiyadi, Teuku; Suryani, Linda (Riset Informasi Kesehatan, 2024)
Background: This stunting prevention dental caries monitoring card is a development model for parenting patterns to prevent stunting in children. These cards were developed with a school child theme and are efficient for children and health practitioners to carry and study. The parenting pattern in the form of a Dental Caries Monitoring Card is expected to prevent caries which can affect food intake and nutritional status. Method: This research uses the Research and Development (R&D) method or research and development. This research was carried out at 77/IV Jambi City. Subject try in research are expert test subjects (material experts and media experts). Group trials carried out on 16 elementary school children at SDN 77/IV Jambi City. Technique Data collection includes expert assessments and responses from elementary school children, with a questionnaire instrument. Trials were carried out to collect data needed as a reference to determine the appropriateness of the quality of the dental caries monitoring card developed. The trials carried out included expert validation tests and group trials primary school children. Results: The Dental Caries Monitoring Card is to prevent dental caries and is a development model for parenting patterns to prevent stunting in elementary school children. Based on the assessment of media and material expert validators, the Dental Caries Monitoring Card media is very suitable for use for dental health promotion as a parenting pattern to prevent stunting in toddlers, with a score of 89.0% for media and 87.9% for material. The response of school age children to the Dental Caries Monitoring Card media was very adequate with a score 88.3%. Conclusion: Producing a product that can be used by children, parents and health practitioners as a medium for developing parenting patterns in the form of dental caries monitoring cards is expected to prevent caries which can affect food intake and nutritional status.